2014
DOI: 10.1002/lary.25038
|View full text |Cite
|
Sign up to set email alerts
|

The time course and microbiology of surgical site infections after head and neck free flap surgery

Abstract: 2b

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 40 publications
4
55
0
Order By: Relevance
“…A mean 15 day interval was noted (range = 6–26 days) before diagnosis of donor site surgical site infection was made. We have previously described the time of onset and microbiology of these donor surgical site infections . No statistically significant associations were noted between the development of donor site surgical infection and the flap harvest site or applicable as previously described independent variables, including ASA, age, and surgical duration.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A mean 15 day interval was noted (range = 6–26 days) before diagnosis of donor site surgical site infection was made. We have previously described the time of onset and microbiology of these donor surgical site infections . No statistically significant associations were noted between the development of donor site surgical infection and the flap harvest site or applicable as previously described independent variables, including ASA, age, and surgical duration.…”
Section: Resultsmentioning
confidence: 91%
“…Twenty‐two of the 64 patients (34.4%) with surgical site infection developed late‐onset surgical site infections (days 15–30 postoperatively), but there was no significant difference in any of the patient or operative characteristics noted above when comparing this group with the early onset (days 1–14 postoperatively) surgical site infection group ( p > .05; chi‐square for categorical variables; Student's t test for continuous variables). We have previously described the time course and microbiology of surgical site infections in a cohort that included the 64 surgical site infections described in this study …”
Section: Resultsmentioning
confidence: 99%
“…Infections of the head and neck following ablative surgery may lead to bacterial colonization of plates, resulting in biofilm formation, wound contamination and subsequent plate exposure requiring hardware removal to eliminate the nidus of infection [32]. Durand et al recently reviewed their experience of SSIs following head and neck free reconstructive surgeries reporting 25% of their swabs growing normal oral flora, 44% gram-negative bacilli, 20% methicillin-resistant Staphylococcus aureus and 16% methicillin-sensitive Staphylococcus aureus [33]. The authors found that in 67% of cultures, at least one pathogen was found to be resistant to prophylactic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show an association between previous radiotherapy and increased risk of SSI, 64,65,69,144,145,147,149 being worse in patients exposed to irradiation doses greater than 60 Gy. 144,145 Suh et al found an association between previous surgery and the risk of developing SSI.…”
Section: Is Antibiotic Prophylaxis Required For Clean-contaminated mentioning
confidence: 99%